Rediscovered Fragments Shed New Light on a Proto-Masoretic Torah Scroll - Sanders, Paul (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2023)
After Edna Engel and Mordechay Mishor had discovered that two fragments with excerpts from the book of Exodus belonged to a single Torah scroll dating from the seventh or eighth century CE, Mordechai Veintrob identified thirteen additional fragments of the same scroll, most of them coming from the Cairo Genizah. This article shows that in the preserved fragments no orthographic differences occur with the (partially reconstructed) text of the more recent Aleppo Codex, while there are such orthographic differences with the other ancient Bible codices. The relationship between the ancient scroll and the Aleppo Codex is looser as far as the sectional division by means of petuḥot and setumot is concerned. However, the tradition according to which five specific lines must be written above the text of the Song of the Sea (Exod 15:1–19) seems to have this very scroll as its source. This tradition was followed in the Aleppo Codex and other ancient codices.